2D β-ketoenamine-linked triazine covalent organic framework photocatalysis for selective oxidation of sulfides. Issue 8 (27th March 2023) - Miao, Xin; Zhang, Fulin; Wang, Yuexin; Dong, Xiaoyun; Lang, Xianjun
Abstract : Blue light-powered aerobic oxidation of organic sulfides sufficiently yields sulfoxides over TpTAPT-COF. Abstract : Triazine could be the onset for photocatalytic materials like 2D (two-dimensional) covalent organic frameworks (COFs). 2D COFs formed by combining β-ketoenamine bonds and triazine are expected to exhibit high photocatalytic activity. In this work, the condensations of 1, 3, 5-triformylphloroglucinol (Tp) and 1, 3, 5-tris(4-aminophenyl)triazine (TAPT) or 1, 3, 5-tris(4-aminophenyl)benzene (TAPB) under solvothermal conditions catalyzed by an organobase afford two 2D β-ketoenamine-linked COFs, namely TpTAPT-COF and TpTAPB-COF. Due to triazines, TpTAPT-COF tends to form crystalline materials more efficiently than TpTAPB-COF. In addition, the closer π–π stacking of the planar layers of TpTAPT-COF contributes to its high stability and steady electron and energy transfer. TpTAPT-COF performs better conversions than TpTAPB-COF for photocatalytic oxidation of organic sulfides. Moreover, sulfoxides are generated in both energy and electron transfer channels during TpTAPT-COF photocatalysis. This endeavor highlights that triazine is viable for constructing 2D COFs for photocatalysis.